Long-term prognosis after percutaneous endoscopic gastrostomy (PEG) - NAKASHIMA, Naomi; SUGINO, Kayoko; OGAWA, Takehiko; KATSUHARA, Yuko; IIDA, Takeshi; YAGITA, Sanae; KUROKAWA, Fumie; OKITA, Yumi; KURATA, Asuka (Jomyaku Keicho Eiyo, 2012)
[Aim] Although percutaneous endoscopic gastrostomy (PEG) has become widespread as a safer method for enteral feeding, few reports of patients' longterm prognosis after PEG have been published. In this study, the survival rate after PEG was investigated, and prognostic predictors in patients with PEG were examined. [Methods] The subjects were 227 patients who had undergone PEG from January 2000 to December 2009 in our hospital. Their outcomes were confirmed by questionnaires sent to the doctors in charge. [Results] 215 cases were followed for an average of 559.2±521.2 days. The survival rate after PEG was 95% at 30 days, 64.4% at 1 year, and 25.1% at 5 years. The survival rate of the group with a history of accidental ingestion was significantly lower than that of the group without. Survival of the group with a pre-gastrostomy serum albumin level >3.0 g/dL or Onodera's PNI >35 was significantly longer than that of the group with albumin <3.0 g/dL or Onodera's PNI <35. There was a large difference in survival between patients with albumin >3.0 g/dL and <3.0 g/dL or PNI >35 and <35 within 1 year after PEG, but no significant difference after 1 year. [Conclusions] A history of accidental ingestion before PEG is an important prognostic predictor after PEG placement. Onodera's PNI and serum albumin are useful in predicting prognosis, especially within 1 year after PEG, but they are not helpful in predicting the long-term prognosis.